EFFORTS TO CONTROL THE CENTER FOR DRUG AND FOOD CONTROL AGAINST CRIME OF ILLEGAL COSMETICS CIRCULATION IN MAKASSAR CITY - Rusni Rauf, Risma Nur Hijriah; Sampurno, Slamet; Azisa, Nur (Tadulako Law Review, 2021)
This study aims to analyze the efforts to tackle the National Center for Drug and Food Control against the crime of illegal cosmetic distribution and to analyze the obstacles faced by the Center for Drug and Food Control in dealing with the crime of illegal cosmetic distribution. This study uses a normative empirical research type using the statutory approach. law and case approach Efforts to tackle the Food and Drug Supervisory Center against the distribution of illegal cosmetics use 2 measures or measures to protect the community, namely: preventive measures; BBPOM Makassar uses the method of conducting routine surveillance every week randomly based on risk analysis and conducting special examinations with the Police. Supervision is carried out before circulation and after the circulation of cosmetic products on the market, socialization in the form of Communication, Information and Education as well as dissemination of information to provide protection to the public in order to develop insight and awareness in buying and consuming good cosmetics, as well as conducting cyber patrols on social media so that BBPOM Makassar is easier to find out the existence of cosmetic sales. The obstacles faced by the Central for Drug and Food Control in dealing with the distribution of illegal cosmetics, namely using 5 factors; legal factors, the Health Law does not say that the minimum sentence given / imposed on the perpetrator of the illegal distribution of cosmetics is law enforcement factors, in terms of the authority of the Makassar BBPOM PPNS is still lacking due to the absence of forced efforts, the coordination of PPNS BBPOM Makassar with agencies is not optimal. other and there is still a lack of civil servants and staff in the field of supervision considering that the BBPOM Makassar work area is very large, the facilities and facilities factor; inadequate for the purposes of investigation and supervision which require huge costs, community factors; the lack of public awareness and insight in buying and consuming good cosmetics, cultural factors; due to technological sophistication and economic progress that has led to crime.